Acute stroke syndromes with isolated hypoperfusion on MRI: a clinical and MRI study - Alonso, Angelika; Szabo, Kristina; Wolf, Marc; Ebert, Anne; Griebe, Martin; Hennerici, Michael G.; Gass, Achim (European neurology, 2016)
Background: Acute stroke syndromes with negative diffusion-weighted imaging (DWI) but extensive perfusion deficits are rare and constitute a diagnostic challenge due to different operational definitions of penumbral hypoperfusion in acute stroke patients based on MRI criteria. Methods: MR profiles of 19 patients presenting with acute stroke syndromes with negative DWI in the presence of an extensive area of hypoperfusion on time-to-peak (TTP) maps of dynamic susceptibility contrast perfusion-weighted imaging (PWI) were analysed. DWI and PWI lesions were quantified and interpreted with regard to the clinical course. Results: Despite the large area of abnormal perfusion on TTP maps, the clinical course was benign (median National Institute of Health Stroke Scale 2 at admission, 0 at discharge). The volume of hypoperfused tissue was significantly smaller on postprocessed TTP maps with a TTP delay of >4 s than on unprocessed TTP maps with manual contrast adjustment. Semiquantitatively assessed TTP lesion volume was associated with the presence of DWI lesions on follow-up. Conclusion: TTP maps are highly sensitive to demonstrate even small-scale perfusion abnormalities. The additional information from TTP delay thresholds indicates critically reduced perfusion and appears to be a good prognostic indicator in combination with MR angiography and symptomatology.